A Case Report Of A Giant Plunging Ranula In A 25-Year-Old Patient: A case report - Kamran, Tafiya Erum; Wali, Hadia; Batool , Samana; Rasheed, Zainab; Ansari, Shayan Shahid (Journal of Rawalpindi Medical College, 2023)
Abstract This case report aims to present an unusual case of a plunging ranula that extended to the superior vertebral body of the T4 vertebrae, we will be elaborating on the patient presentation, investigations, diagnosis, and treatment of the lesion, while also talking about the adversities faced while diagnosing and treating the patient. The rarity of this condition and an atypical presentation makes this a difficult case to diagnose and vigilant treatment is needed to prevent any complications associated with the condition and ensure a successful treatment and recovery.